2017
DOI: 10.1002/dvdy.24489
|View full text |Cite
|
Sign up to set email alerts
|

A wide temporal window for conjunctival papillae development ensures the formation of a complete sclerotic ring

Abstract: Papilla regeneration is a mechanism that ensures the formation of a complete sclerotic ring and provides another level of redundancy for the induction of a complete sclerotic ring during the normal inductive period. Developmental Dynamics 246:381-391, 2017. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…We were not able to test whether the deficits suggestive of impaired migration identified here lead to long-term motor and/or cognitive deficits. However, our previous studies have shown that IUGR guinea pigs demonstrate altered sensorimotor gating in adolescence assessed using prepulse inhibition of the acoustic startle response [56]. Although not a cognitive test per se, such abnormalities in sensorimotor gating are considered predictive of, or may lead to, cognitive deficits [57].…”
Section: Discussionmentioning
confidence: 99%
“…We were not able to test whether the deficits suggestive of impaired migration identified here lead to long-term motor and/or cognitive deficits. However, our previous studies have shown that IUGR guinea pigs demonstrate altered sensorimotor gating in adolescence assessed using prepulse inhibition of the acoustic startle response [56]. Although not a cognitive test per se, such abnormalities in sensorimotor gating are considered predictive of, or may lead to, cognitive deficits [57].…”
Section: Discussionmentioning
confidence: 99%
“…As each placode is induced, it undergoes morphological development to form a distinct papilla, which renders it inductively active. 79 This regenerative potential is present from HH30 to HH35; by HH35 induction of the underlying scleral condensations, it is fully underway. This skeletogenic induction event occurs beginning at HH34 through to HH36.…”
Section: Morphological Evidencementioning
confidence: 99%
“…[2][3][4] In the chicken, this papilla is visible at Hamburger and Hamilton (HH) stage 30. 4,74,79 Once the conjunctival papillae have completed their inductive role, they degenerate. 4,74 Although this spatiotemporal patterning is still poorly understood, Fyfe and Hall 78 provided evidence for an initial mesenchymal signal that induces each placode, similar to other cutaneous placodal systems.…”
Section: Morphological Evidencementioning
confidence: 99%
See 2 more Smart Citations